Eksplorasi Ragam Nilai Karakter Bangsa Berbasis Kearifan Lokal dalam Motif Batik Khas Banyuwangi - Reri Okta Primanata; Harjianto Harjianto; Moh Sabiq Irwan H (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Local wisdom is diversity in the form of social practices which are based on wisdom from culture. The form of local wisdom in society can be in the form of culture (values, norms, ethics, beliefs, customs, customary laws, and special rules. The batik motifs embodied in Banyuwangi batik are not only an aesthetic manifestation of decorative styles but also have noble values. Banyuwangi community embraced. The purpose of this research is to find out how the philosophy of Banyuwangi's typical batik motifs and also how the relationship between Banyuwangi batik motifs and the national character values. The research method used in this research is qualitative. Cluring Banyuwangi Regency.The data analysis technique used is an interactive analysis technique which includes data collection, data reduction, data presentation, then drawing a conclusion. The result of this research is that the elephant oling batik motif can shape the character of the person seen from its meaning that teaches about the value of goodness. This can be proven in every philosophy contained in every oling elephant batik motif, starting from the coconut leaf motif symbolizing that humans must be like coconut everything has benefits, the jasmine leaf pattern symbolizes that we must be pure, clean, and sincere, the dilem leaf motif comes from a kind. bush plants that can grow anywhere and have medicinal properties, and the elephant's trunk motif symbolizes the greatness of God Almighty, so that the philosophy contained in the oling elephant motif reflects the values of Pancasila, because hierarchically the pyramid of Pancasila, the first precept of God Almighty animate the four principles of Pancasila, which means that humans believe and respect God Almighty as the foundation of faith in living their daily lives.